Tax Policy Changes and their Impact on Tax Revenue: A Case Study in Sri Lanka - Anojan, V. (International Science Congress Association, 2014)
The tax revenue is one of the major sources of income in every government. Tax policy changes play an important role in the country’s tax revenue. The main purpose of this study is to find out the impact of tax policy changes on tax revenue of Sri Lanka. Data on the tax revenue and tax policy changes were collected from the year 1990 to 2012 for this study purpose. Correlation and regression analysis were performed in this study to analyze the hypothesis of the study. The results reflect that there is significant association between tax policy changes and tax revenue of the country (P < 0.01). The regression analysis confirmed that there is significant impact of tax policy changes on tax revenue of Sri Lanka furthermore the regression analysis’s R2 revealed that tax policy changes impact by 49.6% on tax revenue of the country (R2 = .496). According to the correlation analysis and regression analysis confirmed that the country’s tax revenue significantly impact and associate by the tax policy changes. Now a day every county is facing the economic crisis all over the world especially the number of developing countries are facing the budget deficit in every budget which is not good for the economic stability and development of Particular County. Here the tax policy changes are one of the major tools to the government to impact the tax revenue as well budget deficit as their needed.
Keywords: Tax policy changes; Impact; Direct tax revenue; Indirect tax revenue; Sri Lanka